KATA SAPAAN BAHASA MINANGKABAU - Misnawati Misnawati (Jurnal Elektronik WACANA ETNIK, 2017)
This article explains the types of greeting words used by Minangkabau people in Ujuang Batuang and how the words are used. The basic technique used in this study is tapping technique, while the advanced technique used in this study is the simak libat cakap (SLC) technique and simak bebas libat cakap (SBLC) technique, continued with note technique.The results found three categories of greeting words used by the Ujuang Batuang community, namely: (1) general greeting words, (2) adat greeting words, and (3) religious greeting words.